Appliance styles and self-destructive behaviors in agents in activity of the National Police of Peru - Solórzano Ramirez, Yossy (2017)
Objectives: The present study aimed to determine if there is an association between attachment styles and self-destructive behaviors in active agents in the Peruvian National Police of Lima, 2016. Materials and Methods: The participants were 404 students of both sexes between the ages of 20 and 30 years old. The instrument used to measure gratitude was the Gratitude Scale, developed by Alarcón (2014) in Lima, Peru. In order to measure happiness, the Happiness Scale, elaborated by Alarcón (2006) in Lima, Peru, was used. It was integrated by four dimensions: positive meaning of life, satisfaction with life, personal fulfillment and joy of life. Results: It was significantly related to happiness (rho =, 324; p <0.01), and with each of its dimensions. Conclusions: Therefore, it is concluded that people who have a high level of gratitude are more likely to experience full happiness.